2021
DOI: 10.3389/fendo.2021.584125
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expressions of Spermatogenic Marker Genes and Spermatogenic Cell Population Caused by Stress

Abstract: Many young adults are in a state of stress due to social and psychological pressures, which may result in male reproductive dysfunction. To provide new insight into this phenomenon, we investigated the effect of stress on the regulation of key genes and biological events in specific stages of spermatogenesis. After establishing rat stress models of different time durations, we observed pathological changes in testis through haematoxylin and eosin staining, and analysed gene expression in testis by RNA-seq, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The authors found that forced swimming stress in a time course equal to or more than the spermatogenesis period, such as 48-50 days in rats, is significantly effective in reducing the sperm count and motility as well as the fertilization capacity. The effect of stress on the regulation of key genes and biological events in specific stages of spermatogenesis has also been investigated (Tian et al, 2021); the study findings suggest that chronic stress causes damaging pathological changes in the testes, dysregulates the marker genes of specific stages of spermatogenesis, and changes the sperm cell population, which may be responsible for male reproductive dysfunction in rats. Our findings revealed that a similar process might be operative even in humans based on a large clinical sample.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that forced swimming stress in a time course equal to or more than the spermatogenesis period, such as 48-50 days in rats, is significantly effective in reducing the sperm count and motility as well as the fertilization capacity. The effect of stress on the regulation of key genes and biological events in specific stages of spermatogenesis has also been investigated (Tian et al, 2021); the study findings suggest that chronic stress causes damaging pathological changes in the testes, dysregulates the marker genes of specific stages of spermatogenesis, and changes the sperm cell population, which may be responsible for male reproductive dysfunction in rats. Our findings revealed that a similar process might be operative even in humans based on a large clinical sample.…”
Section: Resultsmentioning
confidence: 99%
“…Since Sertoli cells are essential for germ cell maintenance and physiology, their persistent alterations during development through to adulthood may affect spermatogenesis and have detrimental consequences for germ cells and fertility. Psychological stress has been reported to reduce fertility in humans ( Bräuner et al, 2020 ) and is known to lead to molecular changes in spermatogenic cells in testis ( Tian et al, 2021 ) and adult sperm in rodents ( Franklin et al, 2010 ; Gapp et al, 2014 ), with the potential to impair metabolism and behavior in the offspring ( Gapp et al, 2014 ). However, the mechanisms by which Sertoli cells may alter germ cells are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Since Sertoli cells are essential for germ cell maintenance and physiology, their persistent alterations during development through to adulthood may affect spermatogenesis and have detrimental consequences for germ cells and fertility. Psychological stress has indeed been reported to reduce fertility in humans (Bräuner et al 2020) and is known to lead to molecular changes in spermatogenic cells in testis (Tian et al 2021) and adult sperm in rodents (Gapp et al 2014;Franklin et al 2010), with the potential to impair metabolism and behavior in the offspring (Gapp et al 2014). However, the mechanisms by which Sertoli cells may alter germ cells are not known.…”
Section: Discussionmentioning
confidence: 99%